A Qualitative Study on Corporate Criminal Liability in Criminal Offenses in Jakarta Waters (An Analysis of Pollution, Smuggling, and Illegal Fishing Cases) - Lucky Ferdiles; Imam Sholikin (Journal Customary Law, 2026)
This study aims to examine corporate criminal liability in various criminal offenses occurring in the waters of Jakarta, particularly cases of marine pollution, smuggling, and illegal fishing. Crimes in the maritime sector increasingly indicate the involvement of corporations, causing not only economic losses but also environmental damage and threats to state sovereignty. However, law enforcement against corporations still faces various challenges, both normative and practical. This research employs a qualitative method with an empirical juridical approach, using case studies, legal document analysis, and interviews with relevant stakeholders. The findings reveal that corporate criminal liability has not been optimally implemented due to difficulties in evidentiary processes, weak coordination among law enforcement agencies, and the absence of clear standards in determining corporate fault. Furthermore, there is a tendency for law enforcement to focus more on individual perpetrators rather than corporations as legal subjects. Therefore, strengthening regulations, enhancing the capacity of law enforcement officials, and harmonizing policies are necessary to improve the effectiveness of criminal law enforcement against corporations in the waters of Jakarta.